Improving Patient Experience and Treatment Adherence in the Adult, Outpatient Hemodialysis Population. Issue 4 (October 2019) - Saunders, Jessica; Ahmadzadeh, Shahram; Bush, Margaret; Wright, Robin; Granger, Bradi
Abstract : Background: The commonly employed medication reconciliation process leaves room for mismanagement of medications in the complex end-stage renal disease patient population. Purpose: The purpose of this quality improvement project was to implement and evaluate a multidisciplinary education and feedback intervention designed to improve self-management for adults with end-stage renal disease. Methods: A pre-post, same subject repeated measures design was used to evaluate the intervention. Laboratory values, vital signs, interdialytic weight gains, dialysis attendance, and questionnaires were used to assess regimen adherence. Results: We observed improvements in patient outcomes including laboratory values, vital signs, and interdialytic weight gains. Significant improvements in process outcomes were also seen, including accuracy of medication lists, dialysis attendance, and use of remote pharmacy services. Conclusions: A comprehensive medication review, with concurrent pharmacist access, represents a time-effective approach to improved self-management and end-stage renal disease outcomes. Abstract : Supplemental Digital Content is Available in the Text.